[HSO3-pmim][CH3SO3] as an Efficient Catalyst for the Synthesis of Xanthenedione Derivatives - Feng, Cheng; Liu, Meng-Xing; Zhang, Hai-Tao; Wang, Chun; Ma, Jing-Jun (Asian Journal of Chemistry, 2013)
Xanthenedione derivatives were prepared through the condensation reaction of aromatic aldehydes with 5,5-dimethyl-1,3-cyclohexanedione promoted by 1-methyl-3-(3-sulfopropyl)imidazolium methyl sulphate, the reaction time was 20-40 min with the yields between 83.0-95.1 %. It is shown that the proposed method is fast, high efficient and environmentally benign.